2019
DOI: 10.2147/idr.s213845
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association between vitamin D and latent tuberculosis infection in the United States: NHANES, 2011–2012</p>

Abstract: Background Latent tuberculosis infection (LTBI) is a precursor of active tuberculosis diseases and an important issue in the United States and worldwide. The association between vitamin D deficiency and LTBI is poorly understood. Methods From 2011 to 2012, the National Health and Nutrition Examination Survey (NHANES) assessed LTBI (according to tuberculin skin testing and QuantiFERON ® -TB Gold In-Tube) and measured serum levels of vitamin D. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
2
7
1
Order By: Relevance
“…At the initiation of our study, we observed most of our patients suffering from active PTB being de cient in vitamin D with average value at 14.2 ± 8.7ng/ml (Normal:25-80 ng/ml). This is in agreement with similar studies across the globe; a study in US adults acknowledged the inverse relationship of vitamin D levels with the risk of latent TB infection (LTBI) (7) and another in Sudan connected low vitamin D Levels with increased risk of PTB (8). In view of its anti-in ammatory and anti-microbial qualities as elucidated by Coussens et al, one can make the assumption for Vitamin D de ciency to be a risk factor for the development of PTB.…”
Section: Discussionsupporting
confidence: 90%
“…At the initiation of our study, we observed most of our patients suffering from active PTB being de cient in vitamin D with average value at 14.2 ± 8.7ng/ml (Normal:25-80 ng/ml). This is in agreement with similar studies across the globe; a study in US adults acknowledged the inverse relationship of vitamin D levels with the risk of latent TB infection (LTBI) (7) and another in Sudan connected low vitamin D Levels with increased risk of PTB (8). In view of its anti-in ammatory and anti-microbial qualities as elucidated by Coussens et al, one can make the assumption for Vitamin D de ciency to be a risk factor for the development of PTB.…”
Section: Discussionsupporting
confidence: 90%
“…If the concentration of Ca 2+ in cells does not increase, Mycobacterium tuberculosis resides in phagosomes are not lysed, thereby resulting in LTBI [ 31 ]. LTBI patients may develop TB in the near or distant future [ 32 ]. Several case–control studies have linked vitamin D deficiency to active disease, although their interpretation is complicated by potential reverse causality [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have provided evidence that vitamin D deficiency is a risk factor for active TB disease 13 – 16 . A few other studies have reported low vitamin D levels in latent TB individuals compared to their controls 17 , 18 . Furthermore, studies have found that TB patients have lower vitamin D levels than other contacts from the same population 4 , 19 , 20 .…”
Section: Introductionmentioning
confidence: 94%